2002
DOI: 10.1001/archpsyc.59.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Dopamine D2 Receptor Binding in the Anterior Cingulate Cortex in Schizophrenia

Abstract: Background:The clinical efficacy of dopamine D 2 receptor antagonism on the psychotic symptoms of schizophrenia has been widely demonstrated. However, most in vivo imaging studies have not been able to detect significant changes in striatal D 2 receptors in schizophrenia. On the other hand, a number of studies have reported abnormalities in the cerebral cortex of schizophrenia. The aim of this study was to examine the extrastriatal D 2 receptors of patients with schizophrenia.Methods: Eleven drug-naive male pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(117 citation statements)
references
References 38 publications
9
106
0
2
Order By: Relevance
“…analysis of the same anterior cingulate cortex ROIs provided plausible binding potential values which were in agreement with previous research (Suhara et al 2002;Hagelberg et al 2004;Talvik et al 2003;Kaasinen et al 2000). Based on the consistent response of the data to the MRTM2 analysis, but not to the Logan model analysis, it was conjectured that high levels of noise were present in the anterior cingulate cortex.…”
Section: Figuresupporting
confidence: 87%
“…analysis of the same anterior cingulate cortex ROIs provided plausible binding potential values which were in agreement with previous research (Suhara et al 2002;Hagelberg et al 2004;Talvik et al 2003;Kaasinen et al 2000). Based on the consistent response of the data to the MRTM2 analysis, but not to the Logan model analysis, it was conjectured that high levels of noise were present in the anterior cingulate cortex.…”
Section: Figuresupporting
confidence: 87%
“…If there is indeed a reduced temporal cortical D 2 receptor density in schizophrenia, this would produce spuriously high levels of dopamine D 2 /D 3 receptor occupancy in patients with schizophrenia when using normal volunteers as control subjects. However, both Suhara et al (2002b) and Talvik et al (2003), using PET with [ 11 C]FLB-457, failed to find significant reductions in temporal cortical D 2 receptor availability in larger samples of 11 and nine patients, respectively. Furthermore, with the exception of the thalamus, we demonstrated a higher extrastriatal than striatal occupancy not only in the temporal cortex but also throughout the brain.…”
Section: Discussionmentioning
confidence: 92%
“…The role of the antagonistic effects of NMDA receptors has been of interest because of hypofunction of glutamatergic neurotransmission in the PFC (Carlsson et al, 1997), and its relationship to dopaminergic dysfunction (Robbins, 1990;Grace, 1991;Deutch, 1992), which has been hypothesized in schizophrenic patients. Recent PET studies have supported dysfunction of the extrastriatal dopaminergic system in schizophrenic patients (Okubo et al, 1997;Abi-Dargham et al, 2002;Suhara et al, 2002). The Okubo et al (1997) The PFC dopaminergic system is also vulnerable to stress.…”
Section: Prefrontal Cortical Da Receptor Changes Measured By Petmentioning
confidence: 99%
“…[ 11 C]NNC112 (Halldin et al, 1998) and [ 11 C]FLB457 (Halldin et al, 1995) have been developed to assess the extrastriatal neocortical receptor D 1 (D 1 R) and D 2 (D 2 R), respectively. Recent PET studies have suggested the dysfunction of the extrastriatal dopaminergic system in schizophrenic patients (Okubo et al, 1997;Abi-Dargham et al, 2002;Suhara et al, 2002).…”
Section: Introductionmentioning
confidence: 99%